Back to the future - Shail, Andrew, 1978-; Stoate, Robin; British Film Institute (London ; New York : BFI : Palgrave Macmillan, 2010)
Placing the film 'Back to the Future' in the context of Reaganite America, this book discusses Zemeckis' film-making technique and its relationship to the 'New New Hollywood', as well as exploring the film's attitudes to teen culture of the 1950s and 1980s and its representation of science, atomic power and time travel.
You're gonna see some serious shit : new new Hollywood in action -- The 1950's and teen culture -- The 1950's imagined in the 1980s -- Film and time -- Conclusion : your kids are gonna love it.
Includes bibliographical references.
Keywords: Back to the future (Motion picture); Performing Arts